EDITORIAL PREFACE (Volume 9, Issue 1, May 2021) - Pangaribuan, Christian Haposan (Journal of Business And Entrepreneurship, 2021)
Journal of Business and Entrepreneurship, Volume 9, Issue 1, May 2021.